Strengthening the Role of the Unified Agricultural Tax in Economic Incentives of the Agro-Industrial Complex - M. E. Kosov; A. O. Zvereva; R. G. Akhmadeev; E. V. Golubtsova (Финансы: теория и практика, 2025)
In the context of countering sanctions from unfriendly countries within the framework of the implementation of the state import substitution program and the food security doctrine, improving measures aimed at developing subjects of the agro-industrial complex is of particular relevance. The purpose of the study is to formulate proposals for improving the mechanism for collecting the Unified Agricultural Tax based on assessing the effectiveness of tax incentives for agricultural producers, using statistical data from the Federal Tax Service of Russia in form No. 5-Unified Agricultural Tax. To achieve this goal, the following tasks were solved: the fiscal and regulatory role of the Unified Agricultural Tax was assessed; tax benefits for agricultural producers were analyzed, including the mechanism for introducing a reduced unified agricultural tax rate in certain regions; The feasibility of applying benefits under the Unified Agricultural Tax was determined using mathematical tools by calculating the pairwise correlation coefficient between the number of registered payers of this tax and the tax payments they paid in the context of federal districts. The methodology used in the study includes the compilation of time series, statistical and correlation analysis of statistical tax reporting data of the Federal Tax Service of Russia in the context of federal districts. Based on the identified scholastic relationship between the number of Unified Agricultural Tax payers and revenues from this tax to the budget system, a conclusion was made about the effectiveness of using this special tax regime in relation to agricultural producers, including regions where preferential rates are applied. The scientific novelty of the research is to increase the efficiency of the provided tax benefits using mathematical tools by analyzing the received tax payments from this category of taxpayers. Efficiency is achieved by reducing shortfalls in budget revenues by narrowing the circle of benefit recipients. Based on a generalization of the results obtained, proposals were made that would allow greater emphasis to be placed on targeting tax preferences to subjects of the agro-industrial complex, manipulating the conditions for their provision, which should strengthen the role of the regulatory function of the Unified Agricultural Tax.